Air pollution exposure, health and performance in elite female soccer players - Beavan, A.; Julian, R.; Gogolla, F.; Härtel, S.; Koehle, M. S. (Frontiers in Sports and Active Living, 2025)
Introduction: Acute exposure to air pollution negatively affects athletes` ability to perform at their best, with a more pronounced impact observed in females. Despite this, the representation of female-only cohorts is lacking. This study investigates how exposure to air pollution impacts performance and well-being of an elite female soccer team.